Respuesta :
For this case we have the following quadratic equation:
[tex]3x ^ 2 + 7x + 4 = 0[/tex]
Where:
[tex]a = 3\\b = 7\\c = 4[/tex]
According to the quadratic formula we have:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
Substituting:
[tex]x = \frac {-7 \pm \sqrt {7 ^ 2-4 (3) (4)}} {2 (3)}\\x = \frac {-7 \pm \sqrt {49-48}} {6}\\x = \frac {-7 \pm \sqrt {1}} {6}\\x = \frac {-7 \pm1} {6}[/tex]
We have two roots:
[tex]x_ {1} = \frac {-7 + 1} {6} = \frac {-6} {6} = - 1\\x_ {2} = \frac {-7-1} {6} = \frac {-8} {6} = - \frac {4} {3}[/tex]
Answer:
[tex]x_ {1} = - 1\\x_ {2} = - \frac {4} {3}[/tex]
Answer:
x = -4/3 x=-1
Step-by-step explanation:
3x^2 + 7x + 4 = 0
Factor the equation
(3x+4) (x+1) = 0
Using the zero product property
3x+4 =0 x+1 =0
3x+4-4=0-4 x+1-1=0-1
3x=-4 x=-1
3x/3 = -4/3
x = -4/3 x=-1